Astra : concerts 1995. - Astra Chamber Music Society (Vic.) (North Melbourne, [Vic.] : Astra Chamber Music Society, 1995)
Poster advertising the Astra Chamber Music Society's 1995 concert season. Front features multiple taupe coloured images of a pair of hands using sign language. "Musical director John McCaughey. A season of four concerts with the Astra Choir." Reverse of the poster gives further details of the concert season, including listing the works to be performed at each concert. Includes perforated tear off section at the foot of poster for subscription and additional images of hands using sign language. Below title on reverse side: Music for voices and instruments and electronic media.
Caption title.
National Library of Australia's copy previously folded in half, shows horizontal fold mark.
Keywords: Astra Chamber Music Society (Vic.) -- Posters; Chamber music groups -- Victoria -- Posters; Concerts -- Victoria -- Posters; Posters, Australian; Australia -- Posters; Australian